Stock Price Determinants in Indonesia’s Energy Sector during the Russia–Ukraine Geopolitical Conflict - Tegar Bagus Anom Kusuma; Naelati Tubastuvi; Wida Purwidianti; Hermin Endratno (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study examines the effects of Return on Assets (ROA), Debt-to-Equity Ratio (DER), Earnings Per Share (EPS), inflation, interest rates, and exchange rates on the stock prices of energy sector companies listed on the Indonesia Stock Exchange during the 2021–2024 Russia–Ukraine conflict period.Method: This study employs a quantitative approach using secondary data obtained from companies’ financial statements. The sample was selected through purposive sampling, resulting in 29 companies and 116 observations. Data were analyzed using a Fixed Effects model with Driscoll–Kraay standard error correction, processed with StataMP 17.Result: The findings indicate that ROA, DER, and exchange rates have a significant positive effect on stock prices. Meanwhile, EPS, inflation, and interest rates do not show significant effects. The Adjusted R² value of 13.84% suggests that the independent variables explain part of the variation in energy sector stock prices.Practical Implications for Economic Growth and Development: These findings provide practical insights for investors and corporate management in understanding internal and external factors that influence stock value. Such understanding may support more efficient investment decisions and strengthen stability in the energy sector, which plays an important role in national economic development.Originality/Value: This study contributes empirical evidence on the Indonesian energy sector during the Russia–Ukraine conflict period.